Crack tip strain evolution and crack closure during overload of a growing fatigue crack - De-Qiang Wang; Ming-Liang Zhu; Fu-Zhen Xuan; Jie Tong (Fracture and Structural Integrity)
It is generally accepted that fatigue crack growth is retarded after an overload, which has been explained either by plasticity-induced crack closure or near-tip residual stress. However, any interpretation of overload effect is insufficient if strain evolution in front of crack tip is not properly considered. The current understanding of overload-induced retardation lacks the clarification of the relationship between crack closure at crack wake and strain evolution at crack tip. In this work, a material with low work hardening coefficient was used to study the effect of overload on crack tip strain evolution and crack closure by in-situ SEM observation and digital image correlation technique. Crack opening displacement (COD) and crack tip strain were measured before and after the overload. It was observed that the evolution of crack tip strain follows the crack opening behaviour behind the crack tip, indicating a smaller influence of overload on micro-mechanical behaviour of fatigue crack growth. After the overload, plastic strain accumulation was responsible for crack growth. The strain at a certain distance to crack tip was mapped, and it was found that the crack tip plastic zone size correlated well with crack growth rate during post-overload fatigue crack propagation.